Studies towards squalene synthase inhibitors: total synthesis of 6,7-dideoxysqualestatin h5 via an alkene-protection strategy - Almohseni, H (2019)
The zaragozic acids/squalestatins are a family of bicyclic tricarboxylic acids, isolated from a series of different fungi. Members of this class of highly oxygenated natural products show potent inhibitory activity against squalene synthase at the last stage of cholesterol biosynthesis, and so represent attractive candidates for cholesterol-lowering drugs. This thesis describes an asymmetric total synthesis of (–)-6,7-dideoxysqualestation H5 (DDSQ), focusing on the use of a bromide substituent to protect the side-chain alkenyl group from electrophilic addition reactions. Specifically, this alkene-protection strategy was used to circumvent an undesired cyclisation reaction during a late-stage acid-catalysed 6,8- to 2,8- dioxabicyclo[3.2.1]octane rearrangement en route to DDSQ. The synthesis addresses several synthetic challenges, including: efficient construction of the requisite alkenyl bromide functionality in the side-chain; preparation of the crucial β-hydroxy- α-ketoester precursor to the 6,8-cycloadduct; and removal of the bromide substituent through stereoselective methylation cross-coupling in the presence of ester and hydroxyl functionalities. After the fruitful total synthesis of DDSQ, further work was carried out to extend the scope of Seebach’s alkylation of dimethyl tartrate acetonide, enabling access to enantiopure dialkylated products. Also, conditions have been developed for epimerising the monoalkylated tartrate products that may find application in the synthesis of other natural products. Furthermore, to address a key synthetic challenge in a previous synthesis of DDSQ, a concise route to synthesise α-diazo-ε-ketoesters was also developed that demonstrates the utility of chemoselective alkene ozonolysis in the presence of a diazo functionality.